Evaluation of hot mix asphalt(HMA) properties compacted at various temperatures - Silas Tirau, Larry (2005)
Hot mix asphalt (HMA) mixture compacted at various temperature has always been a concern to researcher. Compaction below the standard compaction temperature may bring reverse effect on HMA properties. Moisture damage of HMA with low temperature referred as striping and this problem become prevalent in recent years. This project is to determine the Marshall properties of compacted mix and moisture susceptibility of mix. In this study asphaltic concrete of wearing course with 14mm nominal maximum aggregate size (ACW14) and 20mm (ACW20) were used and test involved were Marshall Test and AASHTO T283 for moisture susceptibility. Samples were compacted at various temperature namely 85ºC, 100ºC, 115ºC, 130ºC, 145ºC, and 160ºC. Result shown that most samples have low density, low flow value and very stiff when compacted at lower temperature. Tensile strength ratio (TSR) for mixes compacted above 115ºC is more than 80% and this shown that mix still stable at minimum temperature of 115ºC for ACW14. ACW20 has TSR more than 80% when compacted at 130ºC and above. This suggests that as mixes get coarser the minimum compaction should be higher. For Marshall Stability, the result indicates that as the compaction temperature increases, the stability increase. However for compaction temperature above 145ºC, the stability slightly drops. This could indicates that 145ºC is the optimum compaction temperature